2021
DOI: 10.31014/aior.1994.04.01.150
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ Perspectives of Service Quality in Community Pharmacies in Nigeria: A Cross-Sectional Survey

Abstract: Background: There is a growing need to understand the determinants of service quality in community pharmacy from the viewpoint of customers. Objectives: The study explored customer perspectives of pharmacy services using quality indicators and proposed a path for quality improvement. Methods: A questionnaire-based cross-sectional survey was conducted on 704 conveniently selected customers of community pharmacies between August and October, 2019. The exit survey examined customer expectations compared to actual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In Table 4, Garrett's scoring method clearly showed that the most important consideration was based on 'quality assurance' with Ranked 1 with the highest score of 63.36; in terms of perceived or known efficacy, safety, awareness of manufacturing standards, the integrity of packaging, storage, in line with the core value of pharmaceutical care. This is by far the most important consideration expected from community pharmacists because the emphasis is on the safety 13,14 and health of the patient consuming the pharmaceutical product 31 . Interestingly, 'Access to credit facility and 'Timeliness of delivery" which were ranked 2 nd and 3 rd respectively are indicative of the expectations of community pharmacists from the supply chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 4, Garrett's scoring method clearly showed that the most important consideration was based on 'quality assurance' with Ranked 1 with the highest score of 63.36; in terms of perceived or known efficacy, safety, awareness of manufacturing standards, the integrity of packaging, storage, in line with the core value of pharmaceutical care. This is by far the most important consideration expected from community pharmacists because the emphasis is on the safety 13,14 and health of the patient consuming the pharmaceutical product 31 . Interestingly, 'Access to credit facility and 'Timeliness of delivery" which were ranked 2 nd and 3 rd respectively are indicative of the expectations of community pharmacists from the supply chain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study explored using quantitative research techniques, the determinants informing buying decisions by community pharmacists in Southwest Nigeria. Community Pharmacists (CPs) are frontline healthcare personnel at the primary healthcare level 13,14 . They are expected to ensure safe, accessible, and affordable medicines.…”
Section: Introductionmentioning
confidence: 99%
“…[PCN, 2020: Ihekoronye et al, 2020. The study purposively selected Lagos, Ogun, and Oyo states respectively because they represent approximately 70% of the population of community pharmacies (1400) in the geographical zone [Ihekoronye et al, 2021;PCN, 2020]…”
Section: Study Population and Settingmentioning
confidence: 99%